ANALISIS ATAS KINERJA FINANSIAL KLUB SEPAKBOLA PROFESIONAL : STUDI KASUS PADA MANCHESTER UNITED PLC - Haryoprasetyo, Riza; Kiswara, Endang (Diponegoro Journal of Accounting, 2013)
Industrial development at the present time has been growing rapidly. Not only the manufacturing industry, services, and banking, but many new industry such as the football industry. In terms of revenue, finance football clubs can be said to be very good. However, many football clubs in European football clubs especially in financial crisis. Unique characteristics of the football industry raises several questions regarding the financial performance of a football club as a whole. This study aims to analyze the main financial components contained in the financial statements of a professional football club, knowing the proper use of financial ratios to measure the financial performance of the football club, and identifying the right industry for the football club. Object of study is the first football club to register his name in the New York Stock Exchange, Manchester United PLC. Results of this study showed that the main components in the financial statements of the football club there are 2, revenue and players’ registration. Manchester United PLC has a pretty good level of profitability, profits increased every year, but liquidity is not good. Manchester United PLC was considered quite solvable. Investment in football clubs is quite profitable, but the risk of debt held pretty big football club.